Assessment of radioactive gaseous effluent released from Ninh Thuan 1 nuclear power plant under scenario of INES-level 6 nuclear accident - Nguyen , Tuan Khai; Le , Dinh Cuong; Do , Xuan Anh; Duong , Duc Thang; Trinh , Van Giap; Nguyen Thi , Thu Ha; Nguyen , Quang Long; Nguyen , Hao Quang; Nguyen , Nam Giang; Le Thi , Hong Hiep; Nguyen , The Phung (Nuclear Science and Technology, 2015)
Based on guides RG 1.109, RG 1.111 published by United States Nuclear Regulatory Commission (USNRC) our research concentrates on assessing radiation doses caused by radioactive substances released from the Ninh Thuan 1 nuclear power plant (NPP) to the environment under scenario of an INES-level 6 nuclear accident caused by the Station Black Out (SBO) incident and the loss of coolant accident (LOCA) phenomenon using software RASCAL4.3 provided by the Emergency Operations Center of USNRC. The NinhThuan 1 plant is assumed to use the VVER-1200 technology with a total power of 2400 MWe. The input data for the model calculations is based on building the accident scenario, the technical parameters of VVER-1200 technology and the meteorology. In this work the meteorological data on dry and rainy seasons which are typical for the NinhThuan region was considered. The maximum dose values were calculated within an area of 40 km radius from the NPP site. The obtained calculation results showed that the dose distributions affected by meteorological conditions. In the rainy season the dose values near the plant are higher than those in the dry season, especially at the distances less than 10 kilometers from the plant the total effective dose equivalence (TEDE) values can be from about 3.5 to 15 times higher than the dose limit for publics. As a result, it is requested to follow the evolution of the accident in order to issue timely the appropriate response measures based on the guidance specified by the Circular 25/2014/TT-BKHCN.